2020
DOI: 10.3390/su12219271
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Sustainability Assessments in the Information Communication Technology Sector in Malaysia

Abstract: The United Nations’ 2030 Agenda has further propelled the need for the private sector to engage with sustainable development. Corporate sustainability research seeks to specifically address this; however, extant literature highlights a paucity of research on how this occurs. In this study, we utilise an emerging process that has been identified to support managers in addressing sustainability—the corporate sustainability assessment (CSA). Utilising an in-depth case study and qualitative data collection, this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…(e.g., References [ 14 16 ]). After World War II, East Asian countries and Southeast Asian countries relied on sufficient manpower to form an economic structure dominated by export processing, which became a production link in the global division of labor (e.g., References [ 17 20 ]). In that process, Japan, South Korea, and Singapore have reached high development levels and become developed countries (e.g., References [ 21 ]).…”
Section: Introductionmentioning
confidence: 99%
“…(e.g., References [ 14 16 ]). After World War II, East Asian countries and Southeast Asian countries relied on sufficient manpower to form an economic structure dominated by export processing, which became a production link in the global division of labor (e.g., References [ 17 20 ]). In that process, Japan, South Korea, and Singapore have reached high development levels and become developed countries (e.g., References [ 21 ]).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned, the second category of papers identified is related to standards & measures, although the lack of indicators to correctly measure the business contribution to sustainable development is still evident (Pranugrahaning et al, 2020), avoiding negative effects such as the greenwashing (Bager & Lambin, 2020). Since the measurement of impact does not entail any punishment or social reward, there is no interest in having the information available (Vázquez‐Maguirre & Benito, 2022).…”
Section: Analysis Of Resultsmentioning
confidence: 99%
“…A corporate sustainability assessment (CSA) is a management process including tools and techniques that are adopted by companies to address sustainability within their business activities [15,16]. It has emerged in response to the practical challenges faced by companies in managing sustainability practices across their business operations.…”
Section: Literature Review: Understanding Corporate Sustainability Pr...mentioning
confidence: 99%
“…More empirical studies across industry sectors and geographical areas are expected to provide more significant value in the research domain as the existing empirical studies in CSA are dominated by the manufacturing sector (for example [6,22]). More in-depth information was identified that examined the intersection between global strategy and local operations, with a specific focus on the Information Communication Technology sector [16]. Empirical studies focusing on financial services, and especially the insurance sector, are needed to support global initiatives related to this sector and its contribution towards achieving sustainable development.…”
Section: Literature Review: Understanding Corporate Sustainability Pr...mentioning
confidence: 99%
See 1 more Smart Citation